Normal reference range of fetal nuchal translucency thickness in pregnant women in the first trimester, one center study - Marzeie Sharifzadeh; Atoosa Adibi; Kimia Kazemi; Silva Hovsepian (Journal of Research in Medical Sciences, 2015)
Background: Considering that establishment of reference value of nuchal translucency (NT)-related to the crown rump length (CRL) during the first trimester will be helpful for determining an appropriate cutoff level for screening of increased NT thickness-related abnormalities, we determined the NT thickness and investigated its relation with different chromosomal and nonchromosomal abnormalities among a large sample size of pregnant Iranian women. Materials and Methods: In this analytic cross-sectional study, pregnant women who were in their first trimester were enrolled at their antenatal visit. Using an abdominal ultrasonography, the fetal NT thickness of the studied population was measured. Those with increased NT thickness were determined. The reference value of NT thickness (5th, 25th, 50th, 75th, and 95th percentiles) within each 5-mm range of CRL and during the 11th, 12th, and 13th gestational weeks were determined. The presences of the different chromosomal and nonchromosomal abnormalities were compared in women with different percentiles of NT thickness who underwent amniocentesis and those who did not. Results: 1,614 pregnant women were evaluated. The mean NT thickness was 1.30 ± 0.54 mm. Increased NT thickness >2 mm and >95th percentile according to their gestational age (GA) was detected in 89 (5.5%) and 58 (3.6%) pregnant women. The reference 95th percentile value range for NT was 1.8-2.35 and increased NT thickness according to our obtained values was associated significantly with chromosomal abnormalities. Conclusion: The obtained reference range in our studied population was different from that reported for other ethnic groups and it is suggested that using this values are more favorable for screening of chromosomal abnormalities during the first trimester of pregnancy than the recommended single cutoff value.